A five-coordinate nickel(II) fluoroalkyl complex as a precursor to a spectroscopically detectable Ni(III) species - Zhang, Cheng-Pan; Wang, Huan; Klein, Axel; Biewer, Christian; Stirnat, Kathrin; Yamaguchi, Yoshitaka; Xu, Long; Gomez-Benitez, Valente; Vicic, David A (Journal of the American Chemical Society, 2013)
Mechanistic proposals for nickel-catalyzed coupling reactions often invoke five-coordinate alkyl- or aryl-bound Ni(II) and/or high-valent nickel(III) species, but because of their reactive nature, they have been difficult to study and fingerprint. In this work, we invoked the stabilizing properties of fluoroalkyl ligands to access such nickel species bearing ligands that are commonplace in organic coupling reactions. We show that five-coordinate Ni(II) complexes containing nickel-carbon bonds can readily be prepared given the appropriate precursor, and we also present evidence for the formation of Ni(III) species upon chemical and electrochemical oxidation of the five-coordinate complexes.